Meningkatkan Hasil Belajar Kimia pada Pokok Bahasan Laju Reaksi melalui Penggunaan Model Pembelajaran Group Investigation (GI) Bagi Siswa Kelas XI IPA 4 SMA Negeri 1 Baros Serang Banten - Lestari, Indiyah (Universitas Mathla'ul Anwar Banten, 2023)
The aim of this classroom action research is to determine the improvement in chemistry learning outcomes on the subject of reaction rates through the use of the Group Investigation (GI) Learning Model for Class XI Science 4 Students at SMA Negeri 1 Baros Serang Banten. The research method was carried out in two cycles, as the object of class XI Science 4 SMA Negeri 1 Baros Serang Banten, totaling 34 people (10 male students, 24 female students). Each cycle has 4 stages, namely planning, implementation, observation and reflection. The data collection method is by collecting test question scores, group work assessment and observation. The benchmark for the success of this research is if the average student learning outcomes reach a minimum of KKM, namely 75, learning completion results reach a minimum of 80%. The results of data analysis obtained after taking action in discussion activities regarding reaction rates through the GI learning model, in the pre-cycle had an average of 70.35 with a completion rate of 44.11% and there were 15 students who completed it). In cycle I the average was 76.61 with a completion rate of 82.35% (28 students completed). In cycle II the average was 80.82 with a completion rate of 100% (34 students completed). Based on data processing, the results of student learning activities in discussion activities experienced an increase. This was proven in the first cycle to have an average achievement of 63.53%. In cycle II the average was 91.46%. Implementation of the GI Model for Class Apart from that, implementing the GI model through learning can: 1) increase learning motivation, 2) increase the courage to ask questions and express opinions, 3) increase students' understanding in group discussion activities.